2017
DOI: 10.1080/14737159.2018.1407243
|View full text |Cite
|
Sign up to set email alerts
|

An update on liquid biopsy analysis for diagnostic and monitoring applications in non-small cell lung cancer

Abstract: Collection of tumor samples is not always feasible in non-small cell lung cancer (NSCLC) patients, and circulating free DNA (cfDNA) extracted from blood represents a viable alternative. Different sensitive platforms have been developed for genetic cfDNA testing, some of which are already in clinical use. However, several difficulties remain, particularly the lack of standardization of these methodologies. Areas covered: Here, the authors present a review of the literature to update the applicability of cfDNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 89 publications
1
33
0
Order By: Relevance
“…The five‐year overall survival rate of NSCLC remains as low as 16% because most patients are already at a locally advanced or metastatic stage when diagnosed . This may be at least partially attributable to inadequate understanding of the pathogenesis of NSCLC and the lack of early diagnostic biomarkers and therapeutic targets . Thus, there is an urgent need to reveal the mechanisms behind the generation and progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The five‐year overall survival rate of NSCLC remains as low as 16% because most patients are already at a locally advanced or metastatic stage when diagnosed . This may be at least partially attributable to inadequate understanding of the pathogenesis of NSCLC and the lack of early diagnostic biomarkers and therapeutic targets . Thus, there is an urgent need to reveal the mechanisms behind the generation and progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…After validation by AccuRef Diagnostics, the sets of unstained slides (A‐D) were distributed to the 17 laboratories; some of the laboratories that specialized in NGS testing of cytological samples had also taken part in the working group of the latest annual meeting on molecular cytopathology held in Naples, Italy (Fig. ) . Each laboratory stained the slides by applying their own routine protocols (Diff Quik, Papanicolaou, or hematoxylin‐eosin staining).…”
Section: Methodsmentioning
confidence: 99%
“…Before its application, there are several challenges, including the major challenge of determining the sensitivity and specificity of ctDNA detection due to its scarcity in the blood when compared to the cfDNA from normal cells [50]. Some studies demonstrated that the quantification and analysis of the cfDNA in the blood during the early disease stages was challenging due to the very low concentration (approximately 0.01%-1%) of the ctDNA fraction [51]. The traditional ctDNA analytic approaches can be broadly divided into amplification and sequencing-based methods.…”
Section: B Cfdna /Ctdnamentioning
confidence: 99%